An architecture design for smart manufacturing execution system. Issue 4 (7th June 2017) - Jeon, Byeong Woo; Um, Jumyung; Yoon, Soo Cheol; Suk-Hwan, Suh
ABSTRACT: MES (Manufacturing Execution System) puts plans given by enterprise system such as ERP(Enterprise Resource Planning) into practice in the shop floor. As contemporary companies are faced with challenge represented by customer-centric market environment and intense competitions, it becomes increasingly important for companies to cope with dynamic customers' demand and shop floor situation rapidly. Even though current MESs gets some improvement on collecting raw data, they fall short of expectation on analyzing data and takes action by cooperating various manufacturing management functions. Furthermore, even though many researches treat data collection, data analysis based on shop floor situation, little number of previous researches deals with collaboration among various functionalities provided by MES. In this paper, we introduce the design of advanced MES (namely Smart MES) for helping MES collect, analyze, take measure by collaborating various functions. This paper consists of two parts. In the first part, current MES problem analysis and corresponding design consideration are presented. In the second part, architecture design of Smart MES is proposed based on design consideration and an operation scenario of TO-BE model is provided for comparison with AS-IS model. GRAPHICAL ABSTRACT: